A formação de professores e os desafios para a educação inclusiva : as experiências da Escola Municipal Leônidas Sobrino Pôrto - Damasceno, Allan Rocha (2006)
In my composition I accomplished a research witch I investigated a teacher formation craving the inclusive school organization. I searched for reasons: How could be possible to democratize the school, if its teachers maintain themselves linked by conservatory hawsers imposed by the ruling thoughts? How can we think about inclusive schools organized by teachers that do not seem to be able to create their own pedagogical practice based on reflective actions? Had the teachers formation (as initial as continuous) contributed for/in the inclusive schools organization? This research was based on, above all, the Theodor Adorno thoughts, an author of Frankfurt School, where I tried discussed the possible teaching staff formation, in current civilizatory stage that is not able to attend the disable students diversity, because its uniquely adaptable dimension has not being capable to make possible to the teachers the necessity reflection development of their autonomy, craving for a emancipation. Consequently the possible teaching staff formation does not perceive the differences of the students, thinking about them, above all, how inherent to the human condition, so making necessary nowadays thinking beyond this, in the quest for limit-breaks impost ignorance near to the specials educational need of the disable students. Having, then, like guide axle the criticism formation of the teachers for the teaching staff autonomy, craving the inclusive schools organization I analyzed some dimensions with the education and emancipation; education and politics; education and sensibility. The school inclusion should happen by the intermediate of the conception change about education, disability and school, between others categories, and not just based on legal apparatus or by some kind of authority actions. Inclusive school movement of disable students is, above all, to sensibilize the teachers by the criticism reflection around their own formation and pedagogical practice. I analyzed too the inclusive education and their possibilities in the development of the solidarity feelings and respect between the teachers and students, disable and not disable, to the access of a emancipative education. The legal reasons that take care of school inclusion of disable students in the regular teaching web were analyzed; the possibilities in the inclusive schools organization; the school inclusion of disable students like a current process; the relation between school inclusion and the prejudice, based on the thoughts of the authors like Crochík and Costa, and others, that make possible to deepen my criticism reflections around the genesis of the prejudice in the society and its manifestation by each human being. I also analyzed the educational aspects that involve the visual, mental and auditory disabilities in view in the studied schools. The results of this study, that was accomplished in a Elementary school of the public web Municipality of Rio de Janeiro, had like subject the adjunct directorship and four teachers of the institution. By the intermediate of interview half structure with the school professionals, it was possible to perceive that the way we must travel over for the inclusive school organization is too long, however necessary. The results got in the locus of my study allows me to conclude that the teacher formation has contributed only a little, excessively, in the combat and the surmount of the exclusion of the disable students, above all scarcity of the debate pointed. Even feeling a kind solitary I the movement of the school inclusion, the schoolteachers utilized the experimentation like one of the resources in the pedagogical doing in front of the demands of the disable students. In the finals considerations, I think that the mainly contribution of my study is the possibility of the criticism about the professional formation, initial and continuous of the teacher that had been predominantly turned to the reproduction of the pedagogical doing, what come hindering retarding the process of the school inclusion of the disable students in the inclusive public school.